What does mathematical problem-solving in the classroom look like through the eyes of a teacher? A personal journey. - Neururer, Roisin (2017)
This dissertation is a self-study in which I explore my beliefs about, and understanding of, problem-solving and its teaching. I examine how my beliefs and understandings evolve through a series of reflective cycles where I planned and taught problem-solving lesson, reflected on my practice and engaged with some of the relevant literature. Audio-recordings of each lesson, my reflective journal, and pupils’ work from the lessons form the main data source of this research. A framework for the analysis of the lessons is developed and the theoretical background for this framework discussed. Analysis revealed the changing nature of my beliefs, particularly around my role as the teacher within the classroom. A greater awareness of the impact student beliefs can have on their approaches to problem-solving also emerged. The implications for my practice and suggestions for further research are discussed.